2014
DOI: 10.1016/j.dld.2014.09.025
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the new antiviral regimens on patient reported outcomes and health economics of patients with chronic hepatitis C

Abstract: Hepatitis C is an important cause of chronic liver disease worldwide with an estimated 170 million people infected. Hepatitis C virus (HCV)-infected patients are physically and mentally impacted by fatigue, depression and anxiety causing an impairment of health related quality of life (HRQOL), lower worker productivity and other patient reported outcomes (PROs). Although anti-HCV regimens containing first generation direct acting antiviral agents (DAAs) were associated with significant side effects, the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 74 publications
3
71
0
1
Order By: Relevance
“…In summary, the current data suggest that significant PRO gains occur with the new DAA treatment regimens regardless of the patient population (coinfected, advanced fibrosis, retreatments, and treatment failures) with the largest gains noted in those patients who obtain SVR [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102]. Therefore, regardless of the treatment needed, SVR should be the goal, not only to improve clinical outcomes, but also to improve patients' experience as documented by improving PRO scores.…”
Section: The Clinical Pro and Economic Implications Of New Anti-hcv mentioning
confidence: 83%
See 3 more Smart Citations
“…In summary, the current data suggest that significant PRO gains occur with the new DAA treatment regimens regardless of the patient population (coinfected, advanced fibrosis, retreatments, and treatment failures) with the largest gains noted in those patients who obtain SVR [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102]. Therefore, regardless of the treatment needed, SVR should be the goal, not only to improve clinical outcomes, but also to improve patients' experience as documented by improving PRO scores.…”
Section: The Clinical Pro and Economic Implications Of New Anti-hcv mentioning
confidence: 83%
“…In contrast, the use of the new interferon-and ribavirin-free all oral regimens for HCV treatment have resulted in significant improvement in patients' HRQOL scores as early as 2 weeks into the treatment, especially in those domains most affected by the hepatitis C virus [physical functioning, work productivity (presenteeism), social functioning, activity]. In fact, by the end of treatment with the DAA's many of the significantly improved scores closely approximated or surpassed the HRQOL scores of the general population without HCV [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101]. These PRO gains have also been observed in patients with both early and advanced fibrosis [90,98].…”
Section: The Clinical Pro and Economic Implications Of New Anti-hcv mentioning
confidence: 85%
See 2 more Smart Citations
“…The improvement in the antiviral efficacy of the new drug regimens promises higher cure rates with fewer side effects and shorter times of treatment compared to the old standard of care, but it is more expensive and requires major investments [55] . Although recent data have demonstrated that treatment of chronic HCV infection with one of the new oral drug regimens can reduce HCV-related complications and is cost-effective in most patients [56] , treating all eligible patients could have an enormous economic impact for both private and public resources [56] .…”
Section: Future Perspectivesmentioning
confidence: 99%